Fenomena Campur Code Masyarakat Banjarmasin pada Aplikasi Tiktok Generasi Z - Nur’Fatimah Az-zahra; Nazwa Ramadhani; Rayhan Zahran Mustofa; Shaffa Helia (Lembaga Pengembangan Kinerja Dosen, 2025)
This study examines the phenomenon of code-mixing among Generation Z in Banjarmasin, particularly in The comments section of TikTok content, which has become a primary digital expression space for young People. The aim of this study was to identify the forms, patterns, and social and cultural factors underlying This linguistic practice. Using descriptive qualitative methods with listening and note-taking techniques, Information was collected from comments on two TikTok posts on the accounts @BudRab and @Fazarbungaz. The findings indicate that the code-mixing that occurred was dominated by the insertion Of Banjarese elements into Indonesian (Banjar-Indonesian code-mixing), as well as a mixture of Banjarese, Indonesian, and English (Outer Code-mixing and Mixed Code-mixing). The forms of code-mixing found Included the insertion of Banjarese words, phrases, and lexical items such as kd (kada), makai, and mun. An analysis of the functions of code-mixing shows that this practice has a dual role: referential (for specific Local contexts), directive (to guide conversations), emotive/expressive (to indicate emotional closeness, for Example, longitude), and most importantly, as a marker of digital identity and cultural solidarity among Banjar speakers in the digital realm. This phenomenon confirms that social media serves as a new, flexible and essential space for the Banjar language to survive and negotiate with global and national languages. This study contributes to sociolinguistics by mapping the dynamics of language evolution among Gen Z in A digital context, highlighting the creative and social aspects of code-mixing.